(untitled) (Eurasian Medical Research Periodical, 2023)
Facilitation (facilitation) in English. "relief", facilis means "to ease" or facilitate). In the management of the facilitator, the participants can solve problems and increase the efficiency of their activities due to their observation and communication with their partners in the team. vocabulary.ru.